2022
DOI: 10.3390/sym14091759
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of MHD Darcy–Forchheimer Hybrid Nanofluid Flow under the Influence of Chemical Reaction and Activation Energy over a Stretching Surface

Abstract: The energy and mass transition through Newtonian hybrid nanofluid flow comprised of copper Cu and aluminum oxide (Al2O3) nanoparticles (nps) over an extended surface has been reported. The thermal and velocity slip conditions are also considered. Such a type of physical problems mostly occurs in symmetrical phenomena and are applicable in physics, engineering, applied mathematics, and computer science. For desired outputs, the fluid flow has been studied under the consequences of the Darcy effect, thermophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Haq et al. [43] documented the Darcy‐Forchheimer hybrid nanofluid flow over a stretching surface. Lee & Yang [44] explained Darcy‐Forchheimer drag modeling for fluid flow across a bank of spherical cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…Haq et al. [43] documented the Darcy‐Forchheimer hybrid nanofluid flow over a stretching surface. Lee & Yang [44] explained Darcy‐Forchheimer drag modeling for fluid flow across a bank of spherical cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…Haq et al. [5] observed the MHD HNF flow over a stretching surface under the influence of chemical reaction and activation energy. Shuaib et al.…”
Section: Introductionmentioning
confidence: 99%
“…Puneeth et al [4] studied the mechanics of a Casson HNF on a bilateral nonlinear expanding sheet with the consequences of mixed convection and Brownian motion. Haq et al [5] observed the MHD HNF flow over a stretching surface under the influence of chemical reaction and activation energy. Shuaib et al [6] described the energy interaction due to the erratic turning disc.…”
Section: Introductionmentioning
confidence: 99%
“…Zeb et al [57] proposed the SBC on Non-Newtonian Ferrofluid over an extending slip. There are many studies [58][59][60] probed the problem of slippage velocity in the flow model. It had a prominent effect in clarifying this effect on the movement of the fluid and its temperature This looks at objectives to fill a familiarity hole withinside the flow and warmth transfer of a radiated Casson HNF with a variable thermal conductivity because the temperature rises, primarily based totally on the literature.…”
Section: Introductionmentioning
confidence: 99%